Strategic Orientation and Performance of Small Businesses in South Africa - Mankgele, Khutso Pitso; Fatoki, Olawale (Journal of Reviews on Global Economics, 2020)
Motivation: Most studies on strategic orientation have focused on financial performance while neglecting social and environmental performance. In this era of sustainable development, the performance of SMEs is better measured using the triple bottom line approach (financial, social and environmental). Studies that examine the effect of strategic orientation on the sustainable performance of SMEs are scarce. Novelty: The aim of the study is to explore the impact of strategic orientation on the sustainable performance of SMEs. While extant studies have explored the effect of strategic orientation on the financial performance of SMEs, this study used the sustainable measure of performance that included financial, social and environmental indicators. Methodology and Methods: The study followed the quantitative research design and a self-administered questionnaire was employed during the data collection process. Data was collected from one hundred and forty SME owners in a cross-sectional survey. The participants of this study were in the retail, service and manufacturing sectors. Data and Empirical Analysis: The Pearson correlation and regression were used for analysis. The Pearson correlation results indicated a positive correlation between strategic orientation and sustainable performance, while the regression analysis showed that strategic orientation has a positive impact on the sustainable performance of SMEs. Policy Considerations: South Africa is a signatory to the Paris Agreement on Climate Change and the United Nations’ Sustainable Development goals. The sustainable performance of SMEs can help to achieve these goals. The findings of this study can help small business owners to continuously acquire strategic orientation education for themselves and their employees. Agencies that support small businesses should organise seminars to train and educate SME owners on strategic orientation and sustainable performance.